2017
DOI: 10.1038/s41467-017-02008-y
|View full text |Cite
|
Sign up to set email alerts
|

Insight into partial agonism by observing multiple equilibria for ligand-bound and Gs-mimetic nanobody-bound β1-adrenergic receptor

Abstract: A complex conformational energy landscape determines G-protein-coupled receptor (GPCR) signalling via intracellular binding partners (IBPs), e.g., Gs and β-arrestin. Using 13C methyl methionine NMR for the β1-adrenergic receptor, we identify ligand efficacy-dependent equilibria between an inactive and pre-active state and, in complex with Gs-mimetic nanobody, between more and less active ternary complexes. Formation of a basal activity complex through ligand-free nanobody–receptor interaction reveals structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
121
3
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(145 citation statements)
references
References 50 publications
16
121
3
3
Order By: Relevance
“…Altogether this leads to poor spectral quality and a lack of correlations in through-bond and NOESY spectra. One of the currently used approaches to address this problem is to perform selective methyl labeling in combination with single site mutations for assignment (Kofuku et al 2012(Kofuku et al , 2014Solt et al 2017;Eddy et al 2018;Xu et al 2019). However, this approach is time-consuming and often ambiguous as mutations may lead to chemical shift changes in other residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether this leads to poor spectral quality and a lack of correlations in through-bond and NOESY spectra. One of the currently used approaches to address this problem is to perform selective methyl labeling in combination with single site mutations for assignment (Kofuku et al 2012(Kofuku et al , 2014Solt et al 2017;Eddy et al 2018;Xu et al 2019). However, this approach is time-consuming and often ambiguous as mutations may lead to chemical shift changes in other residues.…”
Section: Discussionmentioning
confidence: 99%
“…b For each additional data type, the number of expected restraints (violet), used to create expected peaklists, the number of observed restraints (green), added as input to FLYA, and the amount of restraints that are part of an assigned spin system (cyan). Expected but not observed (false negative; orange) or observed but not expected (false positives; yellow) restraints indicate disagreements between measurement and model These observations can be used as a proxy for backbone dynamics as low signal intensities preclude performing conventional relaxation experiments (Solt et al 2017).…”
Section: Assessment Of Assignments and Restraintsmentioning
confidence: 96%
“…We similarly used 19 F NMR to show that pharmacologically distinct PPARγ ligands differentially affect the conformation of the AF-2 helix using a 19 F NMR reporter molecule attached to helix 12, and the conformations we observed are predictive of ligand efficacy (Chrisman et al 2018). Furthermore, using selective labeling approaches and two-dimensional NMR, other work has revealed the existence of ligand-bound conformational states that exist in the continuum between the inactive/ground state and fully active conformations previously captured in crystal structures (Bokoch et al 2010, Kofuku et al 2012, Nygaard et al 2013, Kofuku et al 2014, Okude et al 2015, Sounier et al 2015, Isogai et al 2016, Clark et al 2017, Solt et al 2017). Among these, most related to our study here is an NMR analysis of backbone amide groups of valine residues in β1-adrenergic receptor (β1AR) bound to structurally diverse agonists and antagonists (Isogai et al 2016), which observed a heterogenous conformational response to the ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The AngII and TRV034 distributions differ only in each conformation's relative population, with TRV034 favoring conformations lacking the full complement of features associated with ''active'' receptors. Spectroscopic data and MD simulations of other GPCRs have suggested that partial agonists similarly drive the equilibrium toward activation intermediates instead of the canonical fully active conformation (Dror et al, 2011;Solt et al, 2017;Ye et al, 2016). It is possible that activation intermediates of some GPCRs may have partial activity toward all transducers, while analogous intermediate conformations of other receptors only interact with certain transducers.…”
Section: Implications For Mechanisms Of At1r Biased Agonistsmentioning
confidence: 99%